The Hemoglobin Levels among Coffee-Consuming Female Adolescents at State Senior High School 3 Denpasar - Susanto, Putu Aliefia Marshanda Nora; Tedjasulaksana, Regina; Utarini, Gusti Ayu Eka (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
The habit of coffee consumption among adolescent girls who are in a growth period and have high iron requirements poses a risk of disrupting hemoglobin status. This study aimed to describe hemoglobin levels among adolescent girls who consume coffee at SMAN 3 Denpasar. The research method used was a quantitative descriptive study with a cross-sectional approach. The population consisted of all adolescent girls who consume coffee at SMAN 3 Denpasar, with a sample of 55 participants selected using proportionate cluster random sampling. The instruments used were interview guidelines and a digital hemoglobin measuring device.The results showed that the majority of respondents (78%) consumed coffee more than 1–2 times per day, 18% consumed coffee 3–4 times per day, and 4% consumed coffee more than 5 times per day. A total of 51% of respondents had hemoglobin levels below 12 g/dL. No respondents were found to have high hemoglobin levels. The majority of respondents consumed espresso-type coffee (56%). Respondents who consumed espresso coffee tended to have low hemoglobin levels. In conclusion, female students who consumed coffee more than five times per day, particularly espresso-type coffee, experienced low hemoglobin levels. It is expected that adolescents pay more attention to their coffee consumption patterns, both in terms of frequency and type of coffee consumed, considering the potential negative impact on hemoglobin levels.